Prediction of dry shrinkage deformation for partially enclosed steel reinforced concrete columns. (December 2021) - Wu, Jie; Zhang, Lin; Li, Yaohan; Dong, You
Abstract: It is essential to predict the long-term deformation of partially enclosed steel reinforced concrete (PSRC) columns employed extensively in modern high-rise buildings. This study aims to evaluate the differences of drying shrinkage deformation between PSRC and plain concrete (PC) columns due to their different moisture diffusion, and propose a modified B3 model to predict the dry shrinkage of PSRC columns considering the hindrance of section steel to moisture diffusion. First, the numerical simulation is conducted to estimate the differences between the PC and PSRC column behaviors by the finite element analysis method, focusing on moisture diffusion. The prediction results indicate that the section steel delays the drying shrinkage deformation of concrete due to its obstruction to moisture diffusion. Then, the B3 model is adjusted to fit the long-term deformation of PSRC columns by introducing two modified coefficients, which are determined by parametric analysis. The analytical results show that the geometry of section steel and the ambient relative humidity are the dominant factors to control the variation of the two modified coefficients. Finally, an experiment is performed to grasp the variation law of moisture in concrete and verify the rationality of the proposed model for predicting the drying shrinkage deformation of PSRC columns. Highlights: Existing shrinkage models overestimate the deformation of PSRC columns. The drying shrinkage behavior between PC and PSRC columns is quite different. Obstruction and sealing effects of steel on moisture diffusion are dominant factors. A modified B3 model is presented to predict the drying shrinkage of PSRC columns. Modified coefficients are affected by section steel and ambient relative humidity.